Dimethyloxallyl glycine-loaded mesoporous bioactive glass/poly(D,L-lactide) composite scaffolds with ultrasound stimulation for promoting bone repair - Han, Lei; Zhao, Chaoqian; Zhu, Yufang; Li, Huang (Frontiers in Bioengineering and Biotechnology, 2024)
Bone tissue engineering is considered the ideal approach for bone repair. Mesoporous bioactive glass (MBG) possesses the characteristics of high drug-loading capacity and bioactivity. Low-intensity pulsed ultrasound contributes to promoting fracture healing and bone defect repair, and dimethyloxalyl glycine (DMOG) is a small molecular inhibitor that can suppress prolyl hydroxylase, reducing the expression of hypoxia-inducible factor. In this study, we proposed to prepare DMOG-loaded MBG/poly(D,L-lactide) composite scaffolds (DMOG-MBG/PDLLA) for promoting bone repair. The effects of ultrasound stimulation and DMOG release on the cell responses of rat bone marrow mesenchymal stem cells (BMSCs) and human umbilical vein endothelial cells (HUVECs) and bone repair in vivo were investigated. The results showed that both ultrasound stimulation and DMOG release could promote the proliferation, adhesion and differentiation of BMSCs and HUVECs, respectively. After the implantation of scaffolds in rat cranial bone defect model for 8 weeks, the results indicated that the combined ultrasound stimulation and DMOG release contributed to the highest ability for promoting bone repair. Hence, the DMOG-MBG/PDLLA scaffolds with ultrasound stimulation are promising for application in bone repair.